VISUALISASI DAMPAK NEGATIF BERMAIN JUDI ONLINE DALAM BIDANG SOSIAL DAN MATERI BERUPA FILM PENDEK - Adrian, Muhammad Yafi; Trihanondo, Donny; Zen, Adrian Permana (Telkom University, 2024)
Abstract: Online gambling involves wagering money or valuable items with the hope of winningsubstantial prizes, heavily reliant on luck. However, if luck is not on one's side, the risk of losing allbets becomes significantly high, even potentially leading to bankruptcy. The ease of accessingonline gambling through electronic devices like phones and computers connected to the internetfurther boosts its popularity. A short film titled